Alpha- and Gamma-Tocopherol Modulates the Amyloidogenic Pathway of Amyloid Precursor Protein in an in vitro Model of Alzheimer’s Disease: A Transcriptional Study - Pahrudin Arrozi, Aslina; Shukri, Siti Nur Syazwani; Mohd Murshid, Nuraqila; Ahmad Shahzalli, Ahmad Baihaqi; Wan Ngah, Wan Zurinah; Ahmad Damanhuri, Hanafi; Makpol, Suzana (Frontiers in Cellular Neuroscience, 2022)
The amyloid precursor protein (APP) processing pathway was altered in Alzheimer’s disease (AD) and contributed to abnormal amyloid-beta (Aβ) production, which forms insoluble interneuron protein aggregates known as amyloid plaques in the brain. Targeting the APP processing pathway is still fundamental for AD modifying therapy. Extensive research has evaluated the protective effects of vitamin E as an antioxidant and as a signaling molecule. The present study aimed to investigate the modulatory effects of different tocopherol isomers on the expression of genes involved in regulating the APP processing pathway in vitro. The screening for the effective tocopherol isomers in reducing APP expression and Aβ-42 was carried out in SH-SY5Y stably overexpressed APP Swedish. Subsequently, quantitative one-step real-time PCR was performed to determine the modulatory effects of selected tocopherol isomers on the expression of genes in SH-SY5Y stably overexpressed three different types of APP (wild-type, APP Swedish, and APP Swedish/Indiana). Our results showed that all tocopherol isomers, especially at higher concentrations (80–100 μM), significantly increased (p < 0.05) the cell viability in all cells group, but only α-tocopherol (ATF) and γ-tocopherol (GTF) significantly decreased (p < 0.05) the APP mRNA level without statistically significant APP protein level, accompanied with a reduced significance (p < 0.05) on the level of Aβ-42 in SH-SY5Y APP Swedish. On the other hand, β- and δ-tocopherol (BTF and DTF) showed no effects on the level of APP expression and Aβ-42. Subsequent results demonstrated that ATF and GTF significantly decreased (p < 0.05) the expression of gene beta-site APP cleaving enzyme (BACE1), APH1B, and Nicastrin (NCSTN), but significantly increased (p < 0.05) the expression of Sirtuin 1 (SIRT1) in SH-SY5Y stably expressed the mutant APP form. These findings suggested that ATF and GTF could modulate altered pathways and may help ameliorate the burden of amyloid load in AD.